KEGIATAN PEMBUMBUNAN DAN PEMBERIAN PUPUK KANDANGKOTORAN LEMBU TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMANWORTEL (Daucus carota L) DI DESA GUNUNG TUA PANYABUNGAN - Erti Kumala Indah; Eka Nurwani Ritonga; Elda Sari Siregar; Samsinar Harahap (Jurnal Transformasi Pendidikan Indonesia, 2026)
The purpose of this community service is as a community training activity on how to hill up and provide cow dung fertilizer for the growth and production of carrot plants (Daucus carotaL). This community service was carried out in Gunung Tua Panyabungan village in collaboration with lecturers from the Muhammadiyah University of South Tapanuli. This activity involved the Dos Niroha Gunung Tua Panyabungan Farmers Group. Carrot planting is a community service carried out using the method of surveying the location of rice fields in the Gunung Tua Panyabungan village area. By providing seeds to be planted and earthing up, the land is processed first. The provision of cow dung manure is processed first. Community service through extension plays a very important role in maintaining environmental sustainability by providing manure. Farmers realize that providing manure can reduce chemical use and is environmentally friendly. This training can improve the welfare of farmers and help the local economy.